Non-dipping blood pressure pattern is associated with cardiovascular events in a 21-year follow-up study - Lempiäinen, Päivi A. (Springer Nature, 2025)
Non-dipping blood pressure (BP) pattern is a predictor for cardiovascular (CV) events and mortality. We evaluated dipping status change and its association with incidence of non-fatal CV events in middle-aged subjects. The OPERA study was carried out during the years 1991-1993, with a follow-up study 21.7 years later. In this study, we included 452 participants with 24-h ambulatory BP measurements (ABPM) available in both surveys. The study population was divided into four groups according to the dipping pattern change: dipping-dipping (n = 152/33.6%), dipping-non-dipping (n = 198/43.8%), non-dipping-dipping (n = 20/4.4%), and non-dipping-non-dipping (n = 82/18.1%). Sixty-five participants experienced a CV event (14.4%) during the 21.7 (SD 0.8) years of follow-up. The incidence of events was highest (28%) in the non-dipping-non-dipping group, and lowest (6.6%) in the dipping-dipping group (p < 0.001). In Cox regression analyses the covariates were age, sex, total cholesterol, hypertension and use of antihypertensive medication, systolic office BP and ambulatory mean or nighttime systolic BP, as well as the change in the variables during the follow-up period. After adjustments, the association of the non-dipping-non-dipping pattern with CV events compared with the dipping-dipping pattern remained significant (HR 4.01; 95% CI 1.89-8.67, p < 0.001). In summary, non-dipping-non-dipping pattern was associated with non-fatal CV events in the long term, and the effect was independent of the conventional risk factors including office and ambulatory BP levels.